A construção de face e a (im)polidez linguística em entrevistas de Veja - Guimarães, Silvia Bragatto (2010)
Interviews are face to face interactions in which the interviewer and the interviewee interact verbally exposing, both, their social self image (the face). Thus, the one involved in the verbal interaction always incurs in the risk of showing what is not wanted and not what is intended to show. To prevent this from occurring, the interlocutors of the conversation adopt strategies that provide the control of the face building , in a double game of preservation and threatening of the self image. The concern to preserve the social image always accompanies individuals, and this phenomenon can be clearly seen in interviews. In this study the focus is in the verbal interaction context in interviews from personas of the national politics to Veja magazine, published in 2008 and 2009. It"s analyzed, in these interviews, how the faces (positive face and negative face) enrolled in the conversation, both interviewer and interviewee, are built, kept and threatened by the interlocutors themselves, by the use or not of linguistics strategies of politeness. The key questions that guide this study are: which politeness strategies are used during the interaction? What are the reasons for not using politeness in the speech of both interviewer and interviewee during the interaction? What does “losing the face” means to each involved in the interaction? If each one"s position, interviewer and interviewee, occupies in this interactions space (where the confrontation is demanded) is not of equality, is it that both will have polite attitudes, protecting their faces?